Adenosquamous carcinoma of the ampulla of Vater: a case report and literature review. Issue 1 (December 2015) - Hoshimoto, Sojun; Aiura, Koichi; Shito, Masaya; Kakefuda, Toshihiro; Sugiura, Hitoshi
Abstract Background Adenosquamous carcinoma of the ampulla of Vater is extremely rare, and its clinicopathological features are limited and described in few previous case reports. Here, we report curative resection of adenosquamous carcinoma of the ampulla of Vater at an early stage. Case presentation An 81-year-old woman was referred to our hospital for investigation of the frequent elevation of hepatic and biliary enzymes and dilatation of the intrahepatic bile ducts. Preoperative examinations revealed an exposed reddish tumor in the ampulla of Vater, which was diagnosed on biopsy to be adenocarcinoma with squamous cell carcinoma component. Pylorus-preserving pancreaticoduodenectomy with regional lymph node dissection was performed. Pathological examinations revealed the presence of two malignant components in the lesion, including poorly differentiated tubular adenocarcinoma and squamous cell carcinoma, without invasion beyond the sphincter of Oddi or into the duodenal submucosa. These squamous cell carcinoma and adenocarcinoma components in the tumor comprised approximately 30 and 70 % of the lesion, respectively. No metastasis into regional lymph nodes was observed, and the patient experienced no tumor recurrence or metastasis until 20 months after surgery. Conclusion We identified only six reported cases of adenosquamous carcinoma of the ampulla of Vater in the English literature, and all of these patients died of recurrence within 14 months after surgery. To the best of our knowledge, this is the first report of adenosquamous carcinoma of the ampulla of Vater that was curatively resected at an early stage. Although more number of studies on clinicopathological findings are required to determine the appropriate surgical indication, we suggest that surgery remains the mainstay therapy for adenosquamous carcinoma of the ampulla of Vater detected at an early stage.